Philosophy, Psychology, and History: George Sidney Brett and the Quest for a Social Science at the University of Toronto, 1910‑1940 - Gauvreau, Michael (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1988)
AbstractBetween his appointment to the department of Philosophy at the University of Torontoin 1908 until his death in 1944, George Sidney Brett directed the bulk of his writing andteaching to the preservation of the relationship between the sciences and the humanities.In the face of the unpalatable extremes of scientific determinism and the revolutionarycelebration of irrationalism, Brett resolutely asserted the unity of knowledge. This, heinsisted, rested upon discovering a point of intersection between nature, mind, andsociety. Brett's writings emphasized the central role of psychology in preserving thisunity. In his estimation, psychology possessed close links to the natural sciences ofphysiology and biology but, more importantly, the study of the human mind was alsovitally related to the traditional humanities of philosophy, history, and literature. Hisbelief — that humanistic, philosophical values underlay the structure of knowledge—points to a fundamental divergence between English-Canadian and Americanuniversities in the early twentieth century. Brett's standpoint was directed to resisting thefragmentation and specialization which characterized the development of the socialsciences in American universities. The fact that Brett and some influential socialscientists at the University of Toronto pursued, until the 1940s, a method of organizingtheir disciplines which preserved the unspecialized, philosophical, and historicalemphases associated with the humanistic ideal, indicates the need to revise explanationsof the rise of the social sciences in English-Canadian universities.